Do biotransformation data from laboratory experiments reflect micropollutant degradation in a large river basin?. (15th May 2023) - Seller, Carolin; Varga, Laura; Börgardts, Elizabeth; Vogler, Bernadette; Janssen, Elisabeth; Singer, Heinz; Fenner, Kathrin; Honti, Mark
Highlights: Field studies highlight omnipresence of >20 pharmaceuticals and industrial chemicals. Coherent laboratory studies on biotransformation, phototransformation and sorption. Bayesian model framework describing transformation kinetics in laboratory and field. Bioavailability-/ biomass-corrected rate constants are transferable across riverine systems. Relative rankings of rate constants agree well between laboratory- and field. Abstract: Identifying a chemical's potential for biotransformation in the aquatic environment is crucial to predict its fate and manage its potential hazards. Due to the complexity of natural water bodies, especially river networks, biotransformation is often studied in laboratory experiments, assuming that study outcomes can be extrapolated to compound behavior in the field. Here, we investigated to what extent outcomes of laboratory simulation studies indeed reflect biotransformation kinetics observed in riverine systems. To determine in-field biotransformation, we measured loads of 27 wastewater treatment plant effluent-borne compounds along the Rhine and its major tributaries during two seasons. Up to 21 compounds were detected at each sampling location. Measured compound loads were used in an inverse model framework of the Rhine river basin to derive k 'bio, field values – a compound-specific parameter describing the compounds' average biotransformation potential during the field studies. To support model calibration, we performed phototransformation and sorption experiments with all the study compounds, identifying 5 compounds that are susceptible towards direct phototransformation and determining K oc values covering four orders of magnitude. On the laboratory side, we used a similar inverse model framework to derive k 'bio, lab values from water-sediment experiments run according to a modified OECD 308-type protocol. The comparison of k 'bio, lab and k 'bio, field revealed that their absolute values differed, pointing towards faster transformation in the Rhine river basin. Yet, we could demonstrate that relative rankings of biotransformation potential and groups of compounds with low, moderate and high persistence agree reasonably well between laboratory and field outcomes. Overall, our results provide evidence that laboratory-based biotransformation studies using the modified OECD 308 protocol and k 'bio values derived thereof bear considerable potential to reflect biotransformation of micropollutants in one of the largest European river basins. Graphical abstract: Image, graphical abstract